2014
DOI: 10.1158/1078-0432.ccr-14-1236
|View full text |Cite
|
Sign up to set email alerts
|

Clever-1/Stabilin-1 Controls Cancer Growth and Metastasis

Abstract: Purpose: Immunosuppressive leukocytes and vasculature are important host cell components regulating tumor progression. Clever-1/Stabilin-1, a multifunctional scavenger and adhesion receptor, is constitutively present on a subset of type II macrophages and lymphatic endothelium, but its functional role in cancer is unknown.Experimental Design: Here, we generated full Clever-1 knockout mice and cell-specific ones lacking Clever-1 either on macrophages or endothelium. We also used anti-Clever-1 antibody therapy t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 36 publications
3
116
0
2
Order By: Relevance
“…To test this hypothesis in vivo, we used Tie-2 Cre and Lys2 Cre strains to generate cell-selective knockouts. We have previously confirmed their selectivity and efficiency in knocking down stabilin-1 (26). We have shown that in our Tie-2 Cre model, stabilin-1 is absent from endothelium (ENDO stab-1 −/− ) but macrophage expression is maintained.…”
Section: Deletion Of Stabilin-1 In Myeloid Cells Is Associated With Asupporting
confidence: 75%
See 1 more Smart Citation
“…To test this hypothesis in vivo, we used Tie-2 Cre and Lys2 Cre strains to generate cell-selective knockouts. We have previously confirmed their selectivity and efficiency in knocking down stabilin-1 (26). We have shown that in our Tie-2 Cre model, stabilin-1 is absent from endothelium (ENDO stab-1 −/− ) but macrophage expression is maintained.…”
Section: Deletion Of Stabilin-1 In Myeloid Cells Is Associated With Asupporting
confidence: 75%
“…Stabilin-1 knockout mice and cell-specific mice were generated as previously described (26). CAG-Dsred*MST 1Nagy/J (stock 005441) were from The Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…In macrophages, stabilin-1 is known to be a good marker for immunosuppressive M2 cells both in vitro and in vivo (13,16,18,19,(31)(32)(33)(34) (19,32). Notably, however, no link between stabilin-1 and the immunosuppressive mechanisms of M2 macrophages has been found earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Selective extravasation of different leukocyte subsets may also be mediated by additional molecules including common lymphatic endothelial and vascular endothelial receptor-1 (CLEVER-1) (135) and Fas ligand (FasL) (136). CLEVER-1, also known as stabilin-1 and FEEL-1, is a multifunctional scavenging receptor expressed constitutively on lymphatic endothelial cells (LECs) and type 2 macrophages and induced by inflammation on blood endothelial cells (137, 138).…”
Section: Role Of the Tumor Vasculature In Immune Cell Exclusionmentioning
confidence: 99%
“…In a mouse model of melanoma, levels of CLEVER-1 correlated with increased infiltration by FoxP3 + T regs and type II macrophages. Following administration of anti-CLEVER-1 antibody, numbers of T regs and type II macrophages were reduced, and there was increased immune activation and decreased tumor growth (135). FasL mediates T cell apoptosis and can be induced on blood vascular endothelial cells in solid tumors by tumor-derived VEGF-A, prostaglandin E2, and IL-10 (136).…”
Section: Role Of the Tumor Vasculature In Immune Cell Exclusionmentioning
confidence: 99%